2020
DOI: 10.1371/journal.pone.0227993
|View full text |Cite
|
Sign up to set email alerts
|

T helper cell-related changes in peripheral blood induced by progressive effort among soccer players

Abstract: The regulatory mechanisms affecting the modulation of the immune system accompanying the progressive effort to exhaustion, particularly associated with T cells, are not fully understood. We analysed the impact of two progressive effort protocols on T helper (Th) cell distribution and selected cytokines. Methods Sixty-two male soccer players with a median age of 17 (16-29) years performed different protocols for progressive exercise until exhaustion: YO-YO (YYRL1) and Beep. Blood samples for all analyses were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 69 publications
8
25
1
Order By: Relevance
“…In the oldest groups, an increase in Th2 cell-related cytokines was seen, yet there were no changes in Th2 cell percentage. Those findings are in line with our previous study, which showed no changes in Th2 cells’ distribution in junior groups of soccer players [ 21 , 22 ]. One of the probable explanations of this observation is that the changes in Th2 cell-related cytokines promote Th17 cell-related pathways of the post-effort immune response.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the oldest groups, an increase in Th2 cell-related cytokines was seen, yet there were no changes in Th2 cell percentage. Those findings are in line with our previous study, which showed no changes in Th2 cells’ distribution in junior groups of soccer players [ 21 , 22 ]. One of the probable explanations of this observation is that the changes in Th2 cell-related cytokines promote Th17 cell-related pathways of the post-effort immune response.…”
Section: Discussionsupporting
confidence: 93%
“…The CD4 + FoxP3 + (Treg) cells are also involved in post-effort immune modulation because of their role as central anti-inflammatory regulators of the immune response [ 16 , 18 ]. The participation of T cells in the modulation of immunity during maximal effort has been described in athletes [ 19 , 20 , 21 , 22 ]. On the other hand, numerous physically active young men, even though they are not professional athletes, use professional training programs to improve their physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…From this viewpoint, it seems that the endurance effort (Beep test) exerts an immunomodulatory effect among young physically active men. This observation is in line with our previous study describing the impact of endurance-type exercise on T cells in the peripheral blood of young soccer players [24,25,27].…”
Section: Discussionsupporting
confidence: 93%
“…We present evidence that each type of effort caused different immune responses in physically active young men regarding the complement system. Knowing that the complement system takes part in the activation and differentiation of T cells, as well as maintaining immunological memory and that different T cell subsets are altered in post-effort immune response depending of the type of exercise [24][25][26][27], it could lead to the speculation that aerobic and anaerobic exercise may have different types of impact on the post-effort susceptibility to upper respiratory illness, which is described as "open window theory". It may be explained by different molecular mechanism with the participation of the complement system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation